PROTECTION IN A BUILD-OPERATE-TRANSFER AGREEMENT ON PRIVATELY-OWNED LAND NOT ACCOMPANIED BY THE GRANTING OF A BUILDING RIGHTS TITLE - Rustam, Riky; Suwardiyati, Rumi (Fakultas Syariah, 2024)
The definition of build-to-transfer agreements in several laws and regulations varies, particularly concerning the objects they govern. However, when associated with build-to-transfer agreements as contracts subject to contract law, complications arise, especially in relation to such agreements involving privately owned land. The determination of specific objects, particularly regarding the duration of build-to-transfer agreements on privately owned land, remains unregulated. Therefore, there is a need to establish legal protections for build-to-transfer agreements on privately owned land that do not include the granting of building rights. This research aims to determine the implementation period of build-to-transfer agreements and to regulate legal protections for such agreements on privately owned land without building rights. The article employs a normative research method with approaches including legal analysis, conceptual exploration, and comparative study. The findings suggest that legal protection can be enhanced by granting building rights on privately owned land, incorporating clauses reflecting the principle of special personality in agreements, and pursuing breach of contract litigation as a final legal recourse. This study contributes significantly to providing legal protection for parties involved in build-to-transfer agreements on private land. Pengertian perjanjian bangun guna serah dalam beberapa peraturan perundang-undangan bervariasi terutama terkait dengan objek yang diatur. Namun, ketika diterapkan sebagai perjanjian yang tunduk pada hukum perjanjian, terdapat tantangan, terutama jika berhubungan dengan perjanjian bangun guna serah atas tanah milik privat. Penetapan objek, khususnya mengenai jangka waktu perjanjian bangun guna serah pada tanah milik privat, masih belum diatur secara spesifik. Oleh karena itu, perlu adanya regulasi perlindungan hukum yang jelas dalam perjanjian bangun guna serah atas tanah milik privat tanpa pemberian hak guna bangunan. Penelitian ini bertujuan untuk menetapkan jangka waktu pelaksanaan perjanjian bangun guna serah serta mengatur perlindungan hukum dalam perjanjian tersebut atas tanah milik privat yang tidak dilengkapi dengan pemberian hak guna bangunan. Metode penelitian yang digunakan adalah pendekatan normatif dengan menggunakan Undang-Undang, pendekatan konseptual, dan pendekatan perbandingan. Hasil dari penelitian ini menyarankan bahwa perlindungan hukum dapat ditingkatkan dengan memberikan hak guna bangunan atas tanah milik privat, menambahkan klausul yang mencerminkan asas personalitas khusus dalam perjanjian, dan mengajukan gugatan wanprestasi sebagai upaya terakhir dalam perlindungan hukum. Penelitian ini diharapkan dapat memberikan kontribusi signifikan dalam meningkatkan perlindungan hukum bagi semua pihak yang terlibat dalam perjanjian bangun guna serah di tanah milik privat.